Characterization of intrinsic hole transport in single-crystal spiro-OMeTAD - Yuan Li (Nature Portfolio, 2017)
Solar Cells: Intermolecular packing and molecular structure determine hole transport How the molecular packing ordering impact the hole-transport mechanism of an important hole-transport material in solid-state-dye-sensitized solar cells and perovskite solar cells is deciphered. A team led by Jean-Luc Brédas at King Abdullah University of Science and Technology performed a theoretical characterization of the hole-transport mechanism in 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenyl-amine)9,9′-spirobifluorene (spiro-OMeTAD), which has been recently reported to exhibit three-order-magnitude enhanced hole mobility in its single crystal phase compared to spin-coated thin films. The results show that hole transport strongly prefers only one crystal axis, along which the characteristics of intermolecular packing and molecular structure determine the pathway of holes through the functional layer. The finding underlines the strong correlation between molecular and crystal structures and intrinsic electronic properties of molecular conductors, and might help guide better design of hole-transport materials for hybrid solar cell devices.